Signaling Interactions in the Adrenal Cortex - Spät, András; Hunyady, László; Szanda, Gergő (Frontiers in Endocrinology, 2016)
The major physiological stimuli of aldosterone secretion are angiotensin II (AII) and extracellular K+ whereas cortisol production is primarily regulated by corticotrophin (ACTH) in fasciculata cells. AII triggers Ca2+ release from internal stores that is followed by store-operated and voltage-dependent Ca2+ entry whereas K+-evoked depolarisation activates voltage-dependent Ca2+ channels. ACTH acts primarily through the formation of cAMP and subsequent protein phosphorylation by protein kinase A. Both Ca2+ and cAMP facilitate the transfer of cholesterol to mitochondrial inner membrane. The cytosolic Ca2+ signal is transferred into the mitochondrial matrix and enhances pyridine nucleotide reduction. Increased formation of NADH results in increased ATP production whereas that of NADPH supports steroid production. In reality, the control of adrenocortical function is a lot more sophisticated with second messengers crosstalking and mutually modifying each other’s pathways. Cytosolic Ca2+ and cGMP are both capable of modifying cAMP metabolism whilst cAMP may enhance Ca2+ release and voltage-activated Ca2+ channel activity. Besides, mitochondrial Ca2+ signal brings about cAMP formation within the organelle and this further enhances aldosterone production. Maintained aldosterone and cortisol secretion are optimized by the concurrent actions of Ca2+ and cAMP, as exemplified by the apparent synergism of Ca2+ influx (inducing cAMP formation) and Ca2+ release during response to AII. Thus, cross-actions of parallel signal transducing pathways are not mere intracellular curiosities but rather substantial phenomena which fine-tune the biological response. Our review focuses on these functionally relevant interactions between the Ca2+ and the cyclic nucleotide signal transducing pathways hitherto described in the adrenal cortex.